Le paysage comme forme politique - Gaillot, Michel (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
The text invites us to re-read the notion of landscape through a vision of ontology under the regime of co-existence. Considering landscape as the “face of poli-tics” – in the sense that it shares the finitude of existence while leaving space for par-ticularities, local, familiar, preserved but never enclosed behind a border – the author invalidates any thought of duality. Landscape imposes itself as a defocused horizon of meaning, where “touch” replaces the supremacy of the sight.